Spectrophotometric Determination of Diltiazem Hydrochloride by Coloured Complex Formation - Antakli, Saad; Sarkis, Nazira; Kabaweh, Mohamad (Asian Journal of Chemistry, 2010)
In present studies, a new spectrophotometric method is developed in order to determine diltiazem hydrochloride which is used as antihypertensive in tablet form. The method is based on the reaction between diltiazem hydrochloride and bromocresol purple to give a yellow complex in acidic medium. The yellow complex is extracted by chloroform. The maximal absorption is at wavelength 408 nm. The linear relationship between the absorbance and the concentration of diltiazem hydrochloride was in the range of (1-20) mg/L with a correlation coefficient R2 = 0.999. The detection limit is 0.5 mg/L, the molar absorption coefficient was 37175 L mol-1 cm-1. This new method has offered a determination of diltiazem hydrochloride without any interference with excipients either in raw material or in tablets with a high accuracy and an authenticity for the analytical results.